Pick-up sticks - Ellis, Sarah (New York : M.K. McElderry Books : Maxwell Macmillan International, 1971)
Thirteen-year-old Polly's rebellion against her unmarried, fiercely independendent mother comes to a head when they must find a new apartment.
Keywords: Mothers and daughters -- Fiction